Controversies in tourism (CABI, 2012)
This book makes a contribution to the understanding of tourism controversies. Its purpose is to provide a platform for open debate and intellectual discourse with a variety of views on perceived controversies or manifest conflicts firstly within tourism (endogenous controversies), but also in the multidimensional contexts of environment and civil society (exogenous contexts). The focus of the book is on established controversies in tourism and new and emerging conflicts, dilemmas, paradoxes and disputes within tourism contexts. The book has 17 chapters, in addition to an introduction and a conclusion.